2021
DOI: 10.1080/2162402x.2021.1892265
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 inhibition with belapectin combined with anti-OX40 therapy reprograms the tumor microenvironment to favor anti-tumor immunity

Abstract: Treatment with an agonist anti-OX40 antibody (aOX40) boosts anti-tumor immunity by providing costimulation and driving effector T cell responses. However, tumor-induced immune suppression contributes significantly to poor response rates to aOX40 therapy, thus combining aOX40 with other agents that relieve tumor-mediated immune suppression may significantly improve outcomes. Once such target is galectin-3 (Gal-3), which drives tumor-induced immunosuppression by increasing macrophage infiltration and M2 polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…The interactions of extracellular Gal not only activate downstream cell signaling pathways but also contribute to environmental reprogramming ( Figure 6 ). For example, increased Gal-3 levels are often detected in cancer patients’ blood, indicating that circulating Gal contributes to microenvironment reprogramming during cancer progression [ 75 , 138 ]. Circulating Gal-3 interacts with endothelial cells, which induce cytokine production that promotes cancer progression [ 139 , 140 ].…”
Section: Galectin In the Microenvironmentmentioning
confidence: 99%
“…The interactions of extracellular Gal not only activate downstream cell signaling pathways but also contribute to environmental reprogramming ( Figure 6 ). For example, increased Gal-3 levels are often detected in cancer patients’ blood, indicating that circulating Gal contributes to microenvironment reprogramming during cancer progression [ 75 , 138 ]. Circulating Gal-3 interacts with endothelial cells, which induce cytokine production that promotes cancer progression [ 139 , 140 ].…”
Section: Galectin In the Microenvironmentmentioning
confidence: 99%
“…However, overall, all of these immune-related functions have provided the rationale for testing whether Gal-3 can potentiate the effect of ICIs. A recent study using belapectin, a polysaccharide polymer that contains galactose and other sugars, has reported that this drug can potentiate the effect of ICIs and anti-OX-40 agonists in preclinical studies of multiple cancer models [ 80 , 81 , 82 ]. Notably, a recent in silico analysis by Takashima and colleagues showed that the genes encoding Gal-3 and Gal-9 were among the top 20 immunotherapy-related genes whose expression was significantly modulated.…”
Section: The Case Of Galectin-3mentioning
confidence: 99%
“…It is noteworthy to mention that although the affinity of carbohydrate-based inhibitors is generally in the micromolar range, which is often considered low for an inhibitor, they have proven to be very effective in inhibiting the function of galectins in vitro and in vivo. A case in point is the in vivo effect of belapectin [ 80 , 81 , 82 ]. Another example is the recently described monosaccharide galactose-based antagonist of human Gal-8.…”
Section: Approaches For Targeting and Delivery Of Galectinsmentioning
confidence: 99%
“…We used GR-MD-02 and GM-CT-01 as dual Galectin-1 / Galectin-3 inhibitors based on in vitro data reporting that the Kds of GM-CT-01 and GR-GM for Galectin-1 and Galectin-3 are similar (30). However, both compounds have been used as if they mainly inhibit extracellular Galectin-3 [GM-CT-01 ( 63)] [GR-MD-02 (64)(65)(66)(67)]. Whether this is a reasonable assumption is not clear: in vitro, GM-CT-01 does interact with Galectin-1, with a domain that does not include the classical carbohydrate-binding site (33).…”
Section: High Molecular Weight Compounds To Inhibit Extracellular Galectin-1 and Galectin-3mentioning
confidence: 99%